2008
DOI: 10.1111/j.1467-9892.2007.00565.x
|View full text |Cite
|
Sign up to set email alerts
|

Bootstrap Unit‐Root Tests: Comparison and Extensions

Abstract: In this paper we study and compare the properties of several bootstrap unit root tests recently proposed in the literature. The tests are Dickey-Fuller or Augmented DF-tests, either based on residuals from an autoregression and the use of the block bootstrap or on first differenced data and the use of the stationary bootstrap or sieve bootstrap. We extend the analysis by interchanging the data transformations (differences versus residuals), the types of bootstrap and the presence or absence of a correction for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 19 publications
2
52
0
Order By: Relevance
“…This indeed shows in the simulations of Palm et al (2006), who have an ARMA(1,1) process as DGP for u t . The empirical size of the block bootstrap tests is seen to depend heavily on the values of the AR parameter and the MA parameter, whereas this sensitivity is much less for the sieve bootstrap tests.…”
Section: The Time Series Bootstrap Methodsmentioning
confidence: 88%
See 3 more Smart Citations
“…This indeed shows in the simulations of Palm et al (2006), who have an ARMA(1,1) process as DGP for u t . The empirical size of the block bootstrap tests is seen to depend heavily on the values of the AR parameter and the MA parameter, whereas this sensitivity is much less for the sieve bootstrap tests.…”
Section: The Time Series Bootstrap Methodsmentioning
confidence: 88%
“…In the simulations conducted by Palm et al (2006), a difference in power is indeed found. However, this difference in power is often accompanied by a difference in size.…”
Section: Residual-or Difference-based Testsmentioning
confidence: 84%
See 2 more Smart Citations
“…Bootstrapping unit-root tests is thus one of the potentially most interesting application of the entropy-based bootstrap method constituting an alternative to standard residual-based bootstrapped unit-root tests (see Palm et al 2007 for a review) which are not easy to apply when the dependence structure of the residuals is difficult to ascertain.…”
Section: Simulation Study Of the Mebbmentioning
confidence: 99%